(untitled) ("Conference on Universal Science Research 2023", 2023)
Many theories have been developed about what methods and approaches to rely on when teaching a foreign language to young children. Today, one of the main tasks of a pedagogue is to use a number of modern methods and methods in teaching a foreign language, especially English, at the lower levels of education.